PENGARUH PENYULUHAN TERHADAP PETERNAK SAPI DI KECAMATAN KAWANGKOAN BARAT - Sondakh, Rinaldo D; Oley, F S; Sondakh, B F.J; Sajow, A S (Universitas Sam Ratulangi, 2019)
THE EXTENSION EFFECT ON ANIMAL SMALLHOLDER FARMERS AT WEST KAWANGKOAN DISTRICT. Study was conducted on April 2019 to evaluate the extension effect on the animal smallholder attitude in changing their skill development at West Kawangkoan district. Samples were determined by purposive sampling method involving 40 smallholders of local beef cattle. Data were analyzed byChi-Square analysis method. The data analyses showed that the expected frequency value ) was 290.35 to the affecting parameter and nothing effectexpectation value was 69.65. For the attitude variable, the expected frequency )value was 225.83 to the affecting parameter and nothing effectexpectation value was 54.17.Moreover, the skill variableshowed that the expected frequency )value was 225.83 to the affecting parameter and nothing effectexpectation value was 54.17.Analysis result of the calculatedwas 49.0954 > tabel of 5.991. The calculatedwasset at the area of . Therefore, it can be concluded that the extension activity at villages of theKanonang I, Kanonang II, Kanonang IV and Kanonang V affected the animal smallholder attitude in changing their skill development at West Kawangkoan district. Keywords : Chi square analysisi, Extension activity, smallholder attitude,